Selective dispersion of multi-walled carbon nanotubes in segmented polyurethane with different melt mixing process - Jirakittidul, Kittimon; Khrongsakun, Krittaya; Khongkhaw, Kannika; Nernplod, Kusuman (My University, 2017)
Polyurethanes (PU) have been widely used in many applications since their properties can be tailored as desire. In order to improve their electrical property, PU is incorporated with multi-walled carbon nanotubes (MWCNT). The effects of different mixing times and temperatures on selective dispersion of MWCNT in segmented PU were studied. Furthermore, segmented PU based on two different soft segments; i.e. polyester (PU-ester) and polyether (PU-ether), were used. PU/MWCNT nanocomposites were prepared by an internal mixer for 4-12 minutes at 190-210°C. FESEM, DSC and LCR meter were used to characterize morphology and thermal properties. It was found that MWCNT were dispersed in soft segment of PU-ether. Good MWCNT dispersion was able to achieve at high temperature with short mixing time or low temperature with long mixing time. On the other hand, PU-ester/MWCNT nanocomposites, MWCNT preferred to disperse in hard segment and could be dispersed well in PU-ester at low mixing temperature.
Keywords: Carbon nanotube and melt mixing; Polyurethanes nanocomposites